The worlds of European constitutionalism - De Burca, G. (Grainne); Weiler, Joseph, 1951- (Contemporary European politics., 2012)
"The issue of constitutional authority, and more particularly the plurality of claims to legal and constitutional authority, has been a dominant theme of European Union legal scholarship in recent years. The resonance of the topic is evident in many of the major EU developments of the past decade: the momentous eastwards enlargement, the gambit of the un-ratified Constitutional Treaty; the growing number of national constitutional court challenges to EU authority claims; the likely EU accession to the European Convention on Human Rights; and finally the rulings of the European Court of Justice on the relationship of EU law to the international legal order"--